Parks for the people : how Frederick Law Olmsted designed America - Partridge, Elizabeth (Viking, an imprint of Penguin Random House LLC., 2022)
"Frederick Law Olmsted longed to make the United States a better, more peaceful place for all, but he didn't know how. In a new country plagued by bitter political divisions, inequality, and greed, how could one person make a difference? Then Fred found his answer: he could build public parks. After winning a contest to design Central Park in the heart of New York City, Fred went on to create visionary designs all across America, including Prospect Park in Boston, Yosemite National Park in California, and even the Capitol Grounds in Washington, DC, where democracy thrives to this day. Fred never stopped working toward his goal of creating common ground for everyone in America. Fred's parks were -- and still are -- designed for all" --